Test-retest reliability of customised inertial measurement units (IMUs) in evaluating skateboarding related manoeuvres - Ab Rasid, A. M.; Musa, A.; Abdullah, M. A.; Abdul Majeed, A. P. P.; Mohd Razmaan, M. A.; Abdullah, M. R.; Abu Osman, N. A.; Musa, R. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Recent developments in sports technology have enabled sports engineers to utilise the availability of inertial measurement units (IMUs) to develop a customised system for data collection during sports performances. Ensuring the reliability of such a system is essential for objective data collection and transmission of information that coaches could rely upon for improving athletes` techniques and overall performance. The aim of this study was to investigate the reliability of a custom-made IMU system (embedded with Arduino Pro Mini) in the evaluation of skateboarding related manoeuvres. A skilful male and experienced amateur skateboarder (23 years, with 5 years skateboarding experience) performed five skateboarding tricks (Ollie, Nollie, Pop Shuvit, Kickflip and Frontside 180) using a customised ORY skateboard (IMUs fused). The skateboarder was permitted to execute two separate tricks (Tests A and B); thereafter, the reliability of the IMUs in recognising the similarity of the tricks was evaluated using a test-retest approach. Six time-domain signals obtained from the IMU system of each trick`s execution were extracted. Statistical analyses, including the Kolmogorov-Smirnov test, intraclass correlation coefficients (ICC), Cronbach alpha and correlation coefficients, were utilised to measure the scale`s reliability of the system. The results revealed no significant difference between Tests A and B of each trick p > 0.05, ICC > 0.80, Cronbach alpha > 0.80 and r > 0.80; p-value < 0.001. A relatively lower root means square error and mean absolute error were obtained, further suggesting the effectiveness of the system in detecting the similarities in the movement patterns of the skateboarder during the trick execution. The IMU system appeared to be reliable in measuring skateboarding tricks performances. The present findings could serve as guidelines for testing future, custom-made, IMU devices before the commencement of data collection.